Morfogênese e taxa de acúmulo de forragem dos capins braúna, cayana e sabiá submetidos ao diferimento - Borges, Gustavo Segatto (2023)
Deferring pasture allows obtaining forage to feed the herd during the off-season. For deferral success, it is necessary to use forage grasses with appropriate characteristics. In this context, an experiment was conducted in the Forage Sector of the Federal University of Uberlândia, in Uberlândia, MG, from March 2021 to July 2022, with the aim of comparing the morphogenesis and forage accumulation of braúna grasses (Urochloa brizantha cv. MG13 Braúna), cayana (Urochloa cv. Cayana) and sabiá (Urochloa cv. Convert 330) submitted to deferment. The experimental design was completely randomized, in a sub-subdivided plot, 3x2x2, with the grasses in the plot, the deferral periods (beginning and end) in the subplots and the experimental year (2021 and 2022) in the subsubplots. The experiment was carried out in plots of 3.5 m x 3.5 m (experimental units) established in 2020. From December 2020 to mid-March 2021 and from September 2021 to mid-March 2022 all plants were maintained with 30 cm high, via weekly cuts. The deferral period, in which the plants remained in free growth (without cuts), was 90 days, from March 20 to June 18, 2021 and 2022. During this period, the morphogenetic evaluation of the three grasses was carried out at the beginning and end of the deferral period. The morphogenetic and structural variables evaluated during the deferral period at tiller level were: the phyllochron (PHY); the leaf elongation rate (LER); the stem elongation rate (SER); the leaf senescence rate (LSR); live leaf blade conversion factor (LLBcF); and the live stem conversion factor (LScF). At forage canopy level, the following were measured: tiller population density (TPD); the leaf growth rate (LGR); the stem growth rate (SGR); the total growth rate (TGR) and the leaf senescence rate (LSR). The deferral period was the factor that most influenced the morphogenesis of grasses. The braúna, cayana and sabiá grasses are suitable for use under deferment.